2011
DOI: 10.1063/1.3665871
|View full text |Cite
|
Sign up to set email alerts
|

Forming-free resistive switching behaviors in Cr-embedded Ga2O3 thin film memories

Abstract: Resistive switching behaviors are studied for the rapid thermal annealing (RTA) Ga 2 O 3 thin film embedding a Cr metal layer. By modifying the thickness, area, and RTA temperature of the device, the thermal-induced resistive switching is similar to those induced by the electrical forming process. The conducting filaments composed of oxygen vacancies are created by the Cr diffusion and oxidization during RTA. The related carrier conduction mechanism obeys space charge limited conduction theory accompanied by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 21 publications
1
25
0
1
Order By: Relevance
“…This oxide is-due to its high gallium excess-a heavily self-doped, n-type semiconductor 29 . Recently, several authors reported that a-GaO x thin films with Pt as TE and ITO or TiN as bottom electrode (BE) reveal a counter figure-eight hysteretic loop in their I-V characteristics 30,31 . They proposed a filamentary switching mechanism, similar to that introduced for TiO x , to explain GaO x switching [30][31][32] .…”
Section: Resultsmentioning
confidence: 99%
“…This oxide is-due to its high gallium excess-a heavily self-doped, n-type semiconductor 29 . Recently, several authors reported that a-GaO x thin films with Pt as TE and ITO or TiN as bottom electrode (BE) reveal a counter figure-eight hysteretic loop in their I-V characteristics 30,31 . They proposed a filamentary switching mechanism, similar to that introduced for TiO x , to explain GaO x switching [30][31][32] .…”
Section: Resultsmentioning
confidence: 99%
“…동결 건조법 [2], 습식 합성법 [3][4][5][6], 물리 기상 증착법 (PVD; physical vapor deposition) 또는 분자선 에피택시 (MBE; molecular beam epitaxy) 증착법과 후속 열처리를 이용한 응집 (agglomeration) 방법 [7][8][9][10], 고전압 이온 건 (gun)을 이용한 이온 임플란테이션(ion implantation) [11,12], 멀티 소스 또는 타겟을 사용한 co-evaporation과 코스퍼터 링 (co-sputtering) 방법 [1,13,14 메모리 [6,7,10,[15][16][17], 저항변화 메모리(ReRAM; resistance random access memory) [4,8,9,13,14,18] …”
Section: 서 론unclassified
“…Interestingly, conductivity of SOP films from Hall effect measurement was greater than that from DC I-V measurement, which was explained by the significant increase of electron density. 메모리 [6,7,10,[15][16][17], 저항변화 메모리(ReRAM; resistance random access memory) [4,8,9,13,14,18 …”
mentioning
confidence: 99%
“…In recent years, reversible resistance switching behaviors in gallium oxide thin films were obtained and investigated [7][8][9][10]. For instance, Gao et al [7] investigated the effect of top electrode materials on bipolar resistive switching behavior of gallium oxide films and pointed out that the migration of oxygen vacancies in the vicinity of the electrode area plays an important role in the resistive switching process.…”
Section: Introductionmentioning
confidence: 99%